Anti-C5a antibody IFX-1 (vilobelimab) treatment versus best supportive care for patients with severe COVID-19 (PANAMO): an exploratory, open-label, phase 2 randomised controlled trial. (December 2020) - Vlaar, Alexander P J; de Bruin, Sanne; Busch, Matthias; Timmermans, Sjoerd A M E G; van Zeggeren, Ingeborg E; Koning, Rutger; ter Horst, Liora; Bulle, Esther B; van Baarle, Frank E H P; van de Poll, Marcel C G; Kemper, E Marleen; van der Horst, Iwan C C; et al.
Summary: Background: Severe COVID-19 is characterised by inflammation and coagulation in the presence of complement system activation. We aimed to explore the potential benefit and safety of selectively blocking the anaphylatoxin and complement protein C5a with the monoclonal antibody IFX-1 (vilobelimab), in patients with severe COVID-19. Methods: We did an exploratory, open-label, randomised phase 2 trial (part of the adaptive phase 2/3 PANAMO trial) of intravenous IFX-1 in adults with severe COVID-19 at three academic hospitals in the Netherlands. Eligibility criteria were age 18 years or older; severe pneumonia with pulmonary infiltrates consistent with pneumonia, a clinical history of severe shortness of breath within the past 14 days, or a need for non-invasive or invasive ventilation; severe disease defined as a ratio of partial pressure of arterial oxygen to fractional concentration of oxygen in inspired air (PaO2 /FiO2 ) between 100 mm Hg and 250 mm Hg in the supine position; and severe acute respiratory syndrome coronavirus 2 infection confirmed by RT-PCR. Patients were randomly assigned 1:1 to receive IFX-1 (up to seven doses of 800 mg intravenously) plus best supportive care (IFX-1 group) or best supportive care only (control group). The primary outcome was the percentage change in PaO2 /FiO2 in the supine position between baseline and day 5. Mortality at 28 days and treatment-emergent and serious adverse events were key secondary outcomes. The primary analysis was done in the intention-to-treat population and safety analyses were done in all patients according to treatment received. This trial is registered at ClinicalTrials.gov (NCT04333420 ). Findings: Between March 31 and April 24, 2020, 30 patients were enrolled and randomly assigned to the IFX-1 group (n=15) or the control group (n=15). During the study it became clear that several patients could not be assessed regularly in the supine position because of severe hypoxaemia. It was therefore decided to focus on all PaO2 /FiO2 assessments (irrespective of position). At day 5 after randomisation, the mean PaO2 /FiO2 (irrespective of position) was 158 mm Hg (SD 63; range 84–265) in the IFX-1 group and 189 mm Hg (89; 71–329) in the control group. Analyses of the least squares mean relative change in PaO2 /FiO2 at day 5 showed no differences between treatment groups (17% change in the IFX-1 group vs 41% in the control group; difference −24% [95% CI −58 to 9], p=0·15. Kaplan-Meier estimates of mortality by 28 days were 13% (95% CI 0–31) for the IFX-1 group and 27% (4–49) for the control group (adjusted hazard ratio for death 0·65 [95% CI 0·10–4·14]). The frequency of serious adverse events were similar between groups (nine [60%] in the IFX-1 group vs seven [47%] in the control group) and no deaths were considered related to treatment assignment. However, a smaller proportion of patients had pulmonary embolisms classed as serious in the IFX-1 group (two [13%]) than in the control group (six [40%]). Infections classed as serious were reported in three (20%) patients in the IFX-1 group versus five (33%) patients in the control group. Interpretation: In this small exploratory phase 2 part of the PANAMO trial, C5a inhibition with IFX-1 appears to be safe in patients with severe COVID-19. The secondary outcome results in favour of IFX-1 are preliminary because the study was not powered on these endpoints, but they support the investigation of C5a inhibition with IFX-1 in a phase 3 trial using 28-day mortality as the primary endpoint. Funding: InflaRx.